Fresno State Women's Softball Team vs. UC Santa Barbara at Old Fenced Field - Watkins, Howard::::::::: (1988)
Fresno State Women's softball team standing on third base line being introduced Red, white and blue plastic triangles hanging on rope for home run "fence"